“Humanist Compatibilism” A Proposal for Reconciliation Between Neuroscience and Criminal Law (Journal of Organizational Psychology, 2020)
This article claims that neither indeterminism nor the so-called neuro-determinism provides an adequate response to the problem of criminal responsibility, highlighting the non-apprehensibility of the problem of freedom and the non-dehumanized image of man. At the same time this contribution proposes a solution from the point of view of humanist compatibilism based on some key assumptions and methodological anchors, such us the rejection of retributivism and the search for unified scientific responses.
Keywords: Organizational Psychology; determinism; free will; compatibilism; neuroscience; excuses